The transcriptional repressor HIC1 regulates intestinal immune homeostasis - Burrows, K; Antignano, F; Bramhall, M; Chenery, A; Scheer, S; Korinek, V; Underhill, T M; Zaph, C (Mucosal immunology, 2017)
The intestine is a unique immune environment that must respond to infectious organisms but remain tolerant to commensal microbes and food antigens. However, the molecular mechanisms that regulate immune cell function in the intestine remain unclear. Here we identify the POK/ZBTB family transcription factor hypermethylated in cancer 1 (HIC1, ZBTB29) as a central component of immunity and inflammation in the intestine. HIC1 is specifically expressed in immune cells in the intestinal lamina propria (LP) in the steady state and mice with a T-cell-specific deletion of HIC1 have reduced numbers of T cells in the LP. HIC1 expression is regulated by the Vitamin A metabolite retinoic acid, as mice raised on a Vitamin A-deficient diet lack HIC1-positive cells in the intestine. HIC1-deficient T cells overproduce IL-17A in vitro and in vivo, and fail to induce intestinal inflammation, identifying a critical role for HIC1 in the regulation of T-cell function in the intestinal microenvironment under both homeostatic and inflammatory conditions.
Keywords: střeva; sliznice; T-Lymphocytes; homeostáza; Animals; Intestines; kultivované buňky; represorové proteiny; Mice, Transgenic; Mice; transkripční faktory Krüppel-like; interleukin-17; Gene Expression Regulation; tretinoin; imunita; Immunity; Cells, Cultured; regulace genové exprese; myši transgenní; Tretinoin; zvířata; Inflammation; Homeostasis; Kruppel-Like Transcription Factors; zánět; Mucous Membrane; Repressor Proteins; Interleukin-17; T-lymfocyty; myši